Analysis of age and lactation specific survival rate, stayability and expected herd life in Sahiwal cattle - UPADHYAY, A; SADANA, D K; GUPTA, A K; SINGH, AVTAR (The Indian Journal of Animal Sciences, 2014)
Demographic analysis was carried out on 830 female calves and 473 cows of Sahiwal breed born between 1985 to 2009 and maintained at the National Dairy Research Institute, Karnal. Survival rate was lowest during 0–1 month of age and was highest during 9–12 months of age. The trend of stayability in female calves up to AFC was declining along with increase in age. Among adult cows the survival rate was 82.0 % in the first lactation and showed decreasing trend up to the fifth lactation. Stayability was noted as 0.421, 0.076 and 0.015 at fourth, eighth and eleventh lactation respectively, indicating that only 42.1, 7.6 and 1.5 % of cows retained in the herd during respective lactations. More than half (58%) of the total cows of first lactation left the herd by the time they completed third lactation; moreover, more than one-fourth (27.82%) of total herd comprised first calvers. It was observed that 79% of total cows present in the herd belonged to first 4 lactations and less than 3% cows belonged to 9 and above lactations, which indicated that this herd of Sahiwal mostly comprised younger cows. The probability of cows being lost from the herd due to their disposal was 0.18 at first lactation, indicating that 18.0 % replacements are required to maintain the herd size constant. Expected herd life was 2.59 lactations more at first lactation and showed decreasing trend along with increase in lactation number.